Larvicidal activity of the essential oil of Pimenta dioica Lindl. front larvae of the Aedes aegypti mosquito (Research, Society and Development, 2020)
This study aimed to evaluate the chemical profile and larvicidal activity of essential oil (EO) extracted from the leaves of Pimenta dioica L. in front of the larvae of the Aedes aegypti mosquito. The EO was extracted by hydrodistillation, with chemical characterization through coupled Gas Chromatography and mass spectrometry (GC-MS). The physicochemical parameters were determined according to the methods described in the Brazilian Pharmacopoeia. The toxicity assay evaluated the lethality of EO against Aedes aegypti. CL50 was calculated for EO action against Aedes aegypti larvae using the Probit method. The larvicidal activity of OE presented mortality at concentrations of 10 to 100 mg L-1 and LC50 of 26,91 mg L-1. The results indicate that the evaluated EO is composed of substances that have a good larvicidal effect against Aedes aegypti,demonstrating its efficiency in combating and controlling the Aedes aegypti mosquito.